Clusters of Tourism Consumers in Romania - Pelau, Corina; Chinie, Alexandra Catalina (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2018)
The analysis and determination of typologies of tourism consumers has been a major concern for scientists, specialists and companies as well. Knowing the demographic and motivational factors that determine consumers to buy tourism products can have a major impact on the marketing strategy by a more efficient targeting of customers. This article presents the results of a research that aims to determine the factors which influence the buying decision for tourism products and the clusters of consumers resulted from these factors. 90 persons have been surveyed pursuing the determination of the most important factors for buying a tourism product and the correlation between them. The factor analysis and the cluster analysis have been applied with the help of the SPSS program. The results of the factor analysis group the items into six factors. In a second phase, the consumers have been divided into three categories based on a hierarchical Ward cluster analysis. The three clusters have been defined and analyzed and recommendations for the future research have been given.